Characterization of Awp14, A Novel Cluster III Adhesin Identified in a High Biofilm-Forming Candida glabrata Isolate - Fernández-Pereira, Jordan; Alvarado, María; Gómez-Molero, Emilia; Dekker, Henk L.; Blázquez-Muñoz, María Teresa; Eraso, Elena; Bader, Oliver; de Groot, Piet W. J. (Frontiers in Cellular and Infection Microbiology, 2021)
Candida glabrata is among the most prevalent causes of candidiasis. Unlike Candida albicans, it is not capable of changing morphology between yeast and hyphal forms but instead has developed other virulence factors. An important feature is its unprecedented large repertoire of predicted cell wall adhesins, which are thought to enable adherence to a variety of surfaces under different conditions. Here, we analyzed the wall proteome of PEU1221, a high biofilm-forming clinical strain isolated from an infected central venous catheter, under biofilm-forming conditions. This isolate shows increased incorporation of putative adhesins, including eight proteins that were not detected in walls of reference strain ATCC 2001, and of which Epa22, Awp14, and Awp2e were identified for the first time. The proteomics data suggest that cluster III adhesin Awp14 is relatively abundant in PEU1221. Phenotypic studies with awp14Δ deletion mutants showed that Awp14 is not responsible for the high biofilm formation of PEU1221 onto polystyrene. However, awp14Δ mutant cells in PEU1221 background showed a slightly diminished binding to chitin and seemed to sediment slightly slower than the parental strain suggesting implication in fungal cell-cell interactions. By structural modeling, we further demonstrate similarity between the ligand-binding domains of cluster III adhesin Awp14 and those of cluster V and VI adhesins. In conclusion, our work confirms the increased incorporation of putative adhesins, such as Awp14, in high biofilm-forming isolates, and contributes to decipher the precise role of these proteins in the establishment of C. glabrata infections.